Knock‐on community impacts of a novel vector: spillover of emerging DWV‐B from Varroa‐infested honeybees to wild bumblebees. (12th June 2019) - Manley, Robyn; Temperton, Ben; Doyle, Toby; Gates, Daisy; Hedges, Sophie; Boots, Michael; Wilfert, Lena
Abstract: Novel transmission routes can directly impact the evolutionary ecology of infectious diseases, with potentially dramatic effect on host populations and knock‐on effects on the wider host community. The invasion of Varroa destructor, an ectoparasitic viral vector in Western honeybees, provides a unique opportunity to examine how a novel vector affects disease epidemiology in a host community. This specialist honeybee mite vectors deformed wing virus (DWV), an important re‐emerging honeybee pathogen that also infects wild bumblebees. Comparing island honeybee and wild bumblebee populations with and without V. destructor, we show that V. destructor drives DWV prevalence and titre in honeybees and sympatric bumblebees. Viral genotypes are shared across hosts, with the potentially more virulent DWV‐B overtaking DWV‐A in prevalence in a current epidemic. This demonstrates disease emergence across a host community driven by the acquisition of a specialist novel transmission route in one host, with dramatic community level knock‐on effects.